2022
DOI: 10.3390/ijms23052672
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Compounds of Natural Origin Target Cellular Receptors to Inhibit Cancer Development and Progression

Abstract: Receptors are macromolecules that transmit information regulating cell proliferation, differentiation, migration and apoptosis, play key roles in oncogenic processes and correlate with the prognoses of cancer patients. Thus, targeting receptors to constrain cancer development and progression has gained widespread interest. Small molecule compounds of natural origin have been widely used as drugs or adjuvant chemotherapeutic agents in cancer therapies due to their activities of selectively killing cancer cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 179 publications
0
8
0
Order By: Relevance
“…The development time and cost of chemically synthesized small molecules are increasing, however. Natural products are pharmacologically active metabolites derived from various plants, animals, or microorganisms ( Wang et al, 2022a ). Natural products offer a number of advantages over biologics, such as a wider range of biological activities, lower side effects and a greater diversity of potent ingredients ( Ma et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The development time and cost of chemically synthesized small molecules are increasing, however. Natural products are pharmacologically active metabolites derived from various plants, animals, or microorganisms ( Wang et al, 2022a ). Natural products offer a number of advantages over biologics, such as a wider range of biological activities, lower side effects and a greater diversity of potent ingredients ( Ma et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have confirmed the capacity of a variety of natural compounds to suppress cancer. Natural compounds exhibit anticancer action via distinct in vivo and ex vivo mechanisms and pathways, such as inducing tumour cell differentiation, triggering cell cycle arrest, promoting tumour cell apoptosis, inhibiting tumour vascular growth, and regulating body immunity, making them essential adjuncts to clinical cancer treatment [16]. Caspase-3 is an important apoptosis marker induced by cytotoxic medicines, radiation, and immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Cytotoxic chemotherapy and radiotherapy are commonly used in the treatment of liver cancer. However, the above two approaches demonstrate significant side effects on the human body in addition to the high price. The development of natural compounds with low toxicity and high efficiency from plants for liver cancer treatment has attracted more and more attention. , Icaritin, a typical isoalenylated flavonoid from herba epimedium, exhibits significant functions for treating liver cancer by delaying the hepatic fibrosis and inhibiting the proliferation of cancer cells. , Recently, icaritin has already passed phase III clinical trials and been approved for sale in January 2022 in China with significant therapeutic effects and safety advantages as a typical and advanced small molecule immunomodulator drug . Moreover, icaritin has been reported to have many other positive pharmacological and biological activities for health care, including anti-breast cancer, anti-rheumatic, and promoting cardiac differentiation and neuronal differentiation of embryonic stem cells. , …”
Section: Introductionmentioning
confidence: 99%
“…2−4 The development of natural compounds with low toxicity and high efficiency from plants for liver cancer treatment has attracted more and more attention. 5,6 Icaritin, a typical isoalenylated flavonoid from herba epimedium, exhibits significant functions for treating liver cancer by delaying the hepatic fibrosis and inhibiting the proliferation of cancer cells. 7,8 Recently, icaritin has already passed phase III clinical trials and been approved for sale in January 2022 in China with significant therapeutic effects and safety advantages as a typical and advanced small molecule immunomodulator drug.…”
Section: Introductionmentioning
confidence: 99%